2021
DOI: 10.3390/su13116133
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Adaptation and Remote Delivery of Undergraduate Research Training during the COVID-19 Pandemic

Abstract: When COVID-19 caused worldwide cancellations of summer research immersion programs in 2020, Mayo Clinic rallied to create an alternate virtual experience called Summer Foundations in Research (SFIR). SFIR was designed not only to ensure the continuance of science pathways training for undergraduate scientists but also to support undergraduate mental wellbeing, given the known pandemic stressors. A total of 170 participants took part in the program and were surveyed pre-post for outcomes in biomedical research … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…This format has effectively retained undergraduates in STEM through their graduate degrees and careers, especially students from minoritized communities [ 8 , 9 ]. In March 2020, the COVID-19 pandemic forced UREs across the U.S. to cancel their summer programs, with few programs pivoting to remote online experiences for summer training [ 7 , 10 12 ]. The pandemic allowed programs to examine the efficacy of online/remote undergraduate research training [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This format has effectively retained undergraduates in STEM through their graduate degrees and careers, especially students from minoritized communities [ 8 , 9 ]. In March 2020, the COVID-19 pandemic forced UREs across the U.S. to cancel their summer programs, with few programs pivoting to remote online experiences for summer training [ 7 , 10 12 ]. The pandemic allowed programs to examine the efficacy of online/remote undergraduate research training [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal study of social work graduate students’ research self-efficacy, Constantine Brown and Park found that student knowledge and research self-efficacy improved between pre-test and post-test on standardized measures and remained significantly improved at follow-up one year later, with no significant difference between online learners and traditional on-site students [ 55 ]. URE program designs remained largely traditional until the COVID-19 pandemic forced a rapid shift to remote online training [ 7 , 10 12 ]. Three studies that measured student and program outcomes after training was completed, found that students reported the virtual program was a positive experience [ 11 , 13 ], and students reported increased interest in pursuing biomedical careers, increases in research skills, positive relationship with mentors, and increased mental wellbeing after virtual program participation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey in the United States reported that 44.5% of research opportunities for undergraduate students were canceled (Grineski, 2020), which left many students without the opportunity to advance their learning and career opportunities. Some undergraduate research institutions adjusted their summer programs to become virtual or created new online programs (Noriega 2020, Valerie Sloan 2020, Afghani 2021, Yowler et al . 2021), but this was not possible for many other programs.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are examining how these changes have impacted student well-being [ 2 , 3 , 4 , 5 ], learning and academic engagement [ 6 , 7 , 8 ], relationships with peers [ 9 ] and longer-term outcomes, such as retention and delayed graduation [ 10 , 11 ]. Few studies have examined how COVID-19 has impacted undergraduate research training [ 12 , 13 , 14 ], and few have focused on initial experiences during the early months of the pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%